To What Extent Can the January 25 Revolution Be Seen as a "Bifurcation" in the Life Stories of Egyptian Migrants in France?. Issue 3 (2nd July 2016) - Lamblin, Celia
ABSTRACT: The revolutionary process initiated in Egypt in 2011 triggered a surge in Egyptian-led organizations in the public arena in Paris. This article examines the issue of the "biographical impacts of commitment" and applies the "life history approach" to these Egyptian activists. Our basic hypothesis is that the opening up of political perspectives in Egypt may be understood as a bifurcation process in such individual trajectories. It may have entailed a series of disruptions in everyday life to the extent of causing these Egyptian migrants to reconsider their positions within the French context.